The Prince Who Loved Me - Hawkins, Karen (New York Pocket Books, 2014)
"Prince Alexsey Romanovin enjoys his carefree life, flirting--and more--with every lovely lady who crosses his path. But when the interfering Grand Duchess Natasha decides its time for her grandson to wed, Alexsey finds himself in Scotland, determined to foil her plans. Brainy, bookish, and bespectacled, Bronwyn Murdoch seems the perfect answer--she isnt at all to the duchesss taste. Living at the beck and call of her ambitious stepmother and social butterfly stepsisters, Bronwyn has little time for a handsome flirt--no matter how intoxicating his kisses are. After all, no spoiled, arrogant prince would seriously be interested in a firm-minded female like herself. So ... wouldnt it be fun to turn his game upside down and prove that an ordinary woman can bring a prince to his knees?"--Page [4] of cover.
Keywords: Princes -- Fiction; Mate selection -- Fiction; Man-woman relationships -- Fiction; Scotland -- Fiction; Romance fiction; Historical fiction